ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN DIVIDEN TUNAI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sudira Putra, I Dewa Gede; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
This study examines the market reaction to the announcement of cash dividend on the company listed in Indonesia Stock Exchange (IDX) 2009-2012. Event study is used in research with ex-dividend date as its events. The market reaction is measured by abnormal returns and average trading volume acticity. The study sample includes 185 announcements of cash dividend of data using purposive sampling method. Analysis of the data used was Wilcoxon test. The analysis showed that there was no significant difference between the abnormal returns before and after the dividend announcement. The same is indicated by the variable average trading volume activity. This means that the dividend announcement does not change the preference of investors to invest.
Keywords: market reaction; dividend announcement; event study